The Influence of Workload and Work Environment on Work Stress with Incentives as a Moderating Variable - Lazuardi, Bayu; Lubis, Fauzi Arif; Daulay, Aqwa Naser (Journal of Social Work and Science Education, 2025)
This study analyzed the influence of workload and work environment on work stress with incentives as a moderating variable among employees of Bakso Bagito in Serbelawan City. This study uses a quantitative approach with an explanatory design and saturated sampling technique on the entire population of 38 employees. Data were collected through questionnaires using a Likert scale and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The research results show that workload has a positive and significant effect on work stress, while the work environment has a negative but not significant effect. Incentives have been proven to moderate the relationship between workload and work stress, but in a positive direction, thus reinforcing the effect of workload on stress. The Adjusted R-Square value of 0.874 indicates that the independent variables are able to explain the variability of work stress substantially. These findings affirm that workload is a dominant factor affecting work stress, while the role of incentives is complex as they can increase psychological pressure if target-based.